Improving Business Performance - S, Ramani (Auerbach Publications, 2018)
No organization is impervious to change. Rather, the survival and growth of an organization is dependent on how well it copes with change. Successful change initiatives consist of the integrated eco-system of its portfolio, programs, and projects. These change initiatives become the delivery mechanisms for implementing the strategy of an organization. Improving Business Performance: A Project Portfolio Management Approach clarifies how the proper application of portfolio, program, and project management concepts can help commercial and non-profit organizations achieve their strategic objectives. Most organizations have been good at devising strategy, but falter during its implementation. Executing strategy well to deliver superior business performance remains a key challenge, which is addressed as the core theme of this book. The book portrays a top-down orientation as well as a bottom-up integration of change initiatives to facilitate alignment to strategy and accommodate mid-course changes. It takes into account existing global best management practices to bring forth an approach that is customizable and useful to organizations in any industry. Describing why portfolio management lies at the apex of change initiative management, the book explains how to design and fine-tune portfolios so they are in alignment with your organization's overall strategy and business needs. After reading this book, you will understand: How to design the project portfolio structure for your organization How to integrate programs and projects within the portfolio more effectively How to better manage interactions across diverse change initiatives How to maintain focus while managing change to realize benefits The book presents a case study that illustrates the application of project portfolio concepts in practical scenarios. It includes chapters dedicated to transition management, change management, benefits management, and the Enterprise Project Management Office. It also includes templates you can immediately put to use in your own portfolios, programs, and projects.